The Effect of Plyometric Box Jump Exercises on Leg Power and Freestyle Swimming Start Speed in Paotere Swimming Club Makassar Athletes - Siti Nurhalizah Mutia Aulria; Charmila Tandi Rerung; Muhammad Syukur (International Journal of Experimental Sports Science Research, 2026)
Backgroud: This study aimed to examine the effect of plyometric box jump training on leg power and 15-meter freestyle start speed among athletes of Paotere Swimming Club Makassar. Methods: The research was conducted in March 2026 at the Universitas Hasanuddin (Unhas) swimming pool, Makassar, using a quantitative pre-experimental method with a one-group pretest-posttest design. Twelve athletes were selected through purposive sampling and completed a six-week plyometric box jump program, three sessions per week, in addition to their regular swimming training. Leg power was measured using the standing broad jump test, while start speed was measured as the time required to cover 15 meters from the starting block. Results: Data were analyzed using the Shapiro-Wilk normality test and paired sample t-test. The results showed a significant improvement in leg power, with the average standing broad jump distance increasing from 1.98 ± 0.15 m to 2.19 ± 0.14 m (t = 6.812, p = 0.000, Cohen's d = 1.97, 95% CI 0.14, 0.28 m), and a significant reduction in 15-meter start time, from 7.45 ± 0.32 seconds to 6.98 ± 0.29 seconds (t = 5.934, p = 0.000, Cohen's d = 1.71, 95% CI -0.64, -0.30 s). Conclusions: These findings indicate that a structured plyometric box jump program can effectively enhance explosive leg power and accelerate the swimming start phase. It is recommended that swimming coaches incorporate periodized plyometric box jump exercises into dryland training to support faster and more powerful starts in freestyle swimming.